Hereditary ectodermal dysplasia and Lyon hypothesis - Camila Helena Machado da Costa; Maria Luiza dos Anjos Pontual; Andréa dos Anjos Pontual; Ricardo Villar Beltrão; Manuella Santos Carneiro Almeida; Michele Baffi Diniz (Editorial Ciencias Médicas, 2015)
Introduction: ectodermal dysplasia refers to disorders that promote dysplasia or aplasia structures and tissues derived from ectoderm. This condition is usually inherited by recessive pattern with lincagem cross, taking their frequency and severity more pronounced in men. Objective: the aim was to report a case of Hereditary Ectodermal Dysplasia. Case report: patient TVLV female, aged 25, leucoderma, which sought a private radiology service in the city of João Pessoa, Paraíba, Brazil. It was reported by the patient, his father, now deceased, was diagnosed with this syndrome. During the extraoral examination, there was dryness of the lips and eyes, skin darkening in the periocular region, hair thin and sparse. The patient did not reveal xerostomia or episodes of hyperthermia. There was loss of vertical dimension, prominent forehead and nails were normal. The clinical examination intrabucal, there was retention of 11 primary teeth and the absence of 19 permanent teeth. The partial oligodontia was then confirmed by radiographic examination. The partial expression of syndromic features can be explained by the Lyon hypothesis (X inactivation), with half of the X chromosomes of patients expressing normal genes and half the abnormal gene. Conclusions: it was recommended genetic counseling and regular visits to the dentist. It´s fundamental the diagnosis of this disorder for the odontologist even in the cases of softening of signs and symptoms.